Test systems in drug discovery for hazard identification and risk assessment of human drug-induced liver injury: Industry-led perspective from EFPIA members of the EU Innovative Medicines Initiative Drug Liver Injury Project, MIP DILI. (3rd July 2017) - Weaver, Richard J.; Betts, Catherine; Blomme, Eric A.G.; Gerets, Helga H.J.; Gjervig Jensen, Klaus; Hewitt, Philip G.; Juhila, Satu; Labbe, Gilles; Liguori, Michael J.; Mesens, Natalie; Ogese, Monday O.; Persson, Mikael; et al.
ABSTRACT: Introduction : The liver is an important target for drug-induced toxicities. Early detection of hepatotoxic drugs requires use of well-characterized test systems, yet current knowledge, gaps and limitations of tests employed remains an important issue for drug development. Areas Covered : The current state of the science, understanding and application of test systems in use for the detection of drug-induced cytotoxicity, mitochondrial toxicity, cholestasis and inflammation is summarized. The test systems highlighted herein cover mostly in vitro and some in vivo models and endpoint measurements used in the assessment of small molecule toxic liabilities. Opportunities for research efforts in areas necessitating the development of specific tests and improved mechanistic understanding are highlighted. Expert Opinion : Use of in vitro test systems for safety optimization will remain a core activity in drug discovery. Substantial inroads have been made with a number of assays established for human Drug-induced Liver Injury. There nevertheless remain significant gaps with a need for improved in vitro tools and novel tests to address specific mechanisms of human Drug-Induced Liver Injury. Progress in these areas will necessitate not only models fit for application, but also mechanistic understanding of how chemical insult on the liver occurs in order to identify translational and quantifiable readouts for decision-making.